Teenagers’ Decision Making About Abortion As An Action To Terminate Unwanted Pregnancy - Hanifa, Fatya Nurul; Anjarwati; Kurniawati, Herlin Fitriani (Universitas Muhammadiyah Sidoarjo, 2020)
Unwanted pregnancy and pregnancy termination generally occurs in adolescents who want to prevent or delay childbirth and have limited access to contraception. Women and girls have unmet contraceptive needs, so that unwanted pregnancies and unsafe abortions are considered normal. The latest data states that 7% of girls aged 15 to 19 will become pregnant and 2% of girls in this age group will have an abortion. Decision making for women before carrying out intentional abortions is influenced by several factors including individual level factors namely marital status, education level, economic independence and whether the woman is a victim of rape or incest. Interpersonal factors such as parent and partner support are also found as influences in decision making, because they have social determinants such as religion and social stigma and norms that exist. The aim of this study was to find out how adolescents make decisions about abortion as an end to unwanted pregnancies.